COVID-19 disease and comorbidity: an outcome? A study on Indian population in a COVID care hospital - Makkar, Namrata; Singla, Amit; Jain, Ajeet; Upreti, Lalendra; Sherwal, B. L. (International Journal of Research in Medical Sciences, 2021)
Background: The world has been severely affected by the novel coronavirus disease (Covid-19). Continuously rising number of cases has put a significant strain on healthcare resources of all countries of the world. Preliminary studies show that people suffering from comorbid conditions are at a relatively higher risk of severe disease and poor outcome. Methods: We studied the risk of ICU admission in 152 Covid-19 positive patients with comorbidity compared to those without comorbid conditions. We studied effect of old age (>65 years), male sex, presence of at least one comorbidity, presence of multiple comorbidities, diabetes mellitus, hypertension, CAD, respiratory disease, neurological disease, skin disease, and hypothyroidism on outcome of coronavirus disease with two tailed Student’s t-test, odds ratio, Chi-square test was used to test significance of results at 95% confidence interval 95% (95% CI). Fisher’s test was also used if one expected value (row total × column total/grand total) was less than 5. Results: In this study, 23 (15.13%) required ICU care. We found higher odds of ICU admission in Covid-19 patients in case of presence of comorbid condition (OR=7.3, 95% CI=2.674, 20.038), diabetes mellitus (OR=2.8, 95% CI=1.035, 8.028), hypertension (OR=1.3, 95% CI=0.396, 4.258), coronary artery disease (OR=2.3, 95% CI=0.430, 12.978) and malignancy (OR=6.5, 95% CI=1.516, 28.54). Case fatality rate (CFR) of those with comorbid conditions was higher (7.55) compared to those without comorbidity (3.03). Conclusions: This study shows that presence of comorbid conditions in Covid-19 positive patients results in significantly higher risk of ICU admission and poor outcome.